What is Evergestis pazukii Alipanah, 2018? (Lepidoptera: Crambidae, Glaphyriinae) - S. Korb (SHILAP, 2021)
Basing on morphology and mtDNA COI sequence data concluded: Evergesris kopetdagensis Kuznetzov, 1958 = E. pazukii Alipanah, 2018, syn. n. Distribution of E. kopetdagensis seemed to be quite wide and covers the area from Van Province in Turkey to Tajikistan and Kyrgyzstan; it is possible that this species occurs also in Turkey eastwards of Van Province, West Afghanistan and Uzbekistan.